Pengaruh Penerapan E-Procurement, Sistem Pengendalian Internal dan Whistleblowing System terhadap Pencegahan Fraud Pengadaan Barang dan Jasa Pemerintah Kabupaten Pasaman Barat - Faradilla, Hanna; Sofyan, Efrizal (Jurnal Nuansa Karya Akuntansi, 2024)
The goal of this research is to determine how internal control, whistleblower policies, and the use of e-procurement can reduce the risk of fraud in the acquisition of goods and services. The research was hosted by 32 Regional Apparatus Organizations in the West Pasaman Regency. Respondents received the PA / KPA, PPK, and PPTK questionnaires—the primary data used in this study—directly. The sampling procedure makes use of the saturated sample technique. This research methodology is multiple regression analysis using SPSS (Statistical Product and Service Solution). According to the results, the West Pasaman Regency government's ability to prevent fraud in its acquisition of goods and services was greatly increased by the implementation of e-procurement and internal control systems, but the whistleblowing system had no such impact.